A comment on "a novel parametric ranking method for intuitionistic fuzzy numbers" - Roohollah Abbasi Shureshjani; Bita Shakouri (Big Data and Computing Visions)
This note shows that the parametric ranking method proposed by Darehmiraki [M. Darehmiraki, A novel parametric ranking method for intuitionistic fuzzy numbers, Iranian Journal of Fuzzy Systems, 16(1) (2019), 129-143] is not correct. By two appropriate examples, we show that the developed index for ranking intuitionistic fuzzy numbers is not suitable and implies wrong results.